1995
DOI: 10.1177/028418519503600319
|View full text |Cite
|
Sign up to set email alerts
|

CNS-Effects from Subarachnoid Injections of Iohexol and the Non-Ionic Dimers Iodixanol and Iotrolan in the Rabbit

Abstract: The neural tolerance of the new non-ionic dimer iodixanol was compared with that of the clinically used monomer iohexol and the dimer iotrolan. Behaviour of non-anaesthetised rabbits was monitored for 3 hours after intracisternal injection, at a dose-volume of I ml/kg of iodixanol 150 mg IIml, iodixanol 320 mg IIml, iohexol 350 mg IIml, or iotrolan 300 mg IIml (10 rabbits in each group). Iotrolan induced generalised seizures in 5 rabbits, iodixanol 320 mg IIml in 2 rabbits, and iodixanol 150 mg IIml in one rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…22 The reported cases of postmyelographic seizure with nonionic, watersoluble contrast in the past decade have been very rare. Although animal studies have shown iopamidol to be more epileptogenic than metrizamide 45 and the excitative neurotoxic potential of iodixanol, 46 clinical trials of these newer nonionic agents have shown them to be safe and effective, with fewer adverse effects than metrizamide. 8,16,22,47 The risk of seizure with the currently used contrast media is reported to be in the range of 0.093%-0.847%.…”
Section: Discussionmentioning
confidence: 99%
“…22 The reported cases of postmyelographic seizure with nonionic, watersoluble contrast in the past decade have been very rare. Although animal studies have shown iopamidol to be more epileptogenic than metrizamide 45 and the excitative neurotoxic potential of iodixanol, 46 clinical trials of these newer nonionic agents have shown them to be safe and effective, with fewer adverse effects than metrizamide. 8,16,22,47 The risk of seizure with the currently used contrast media is reported to be in the range of 0.093%-0.847%.…”
Section: Discussionmentioning
confidence: 99%